Predictors of Polypharmacy Among Elderly Patients in China: The Role of Decision Involvement, Depression, and Taking Chinese Medicine Behavior - Chen, Chaoyi; Feng, Zhanchun; Fu, Qian; Wang, Jia; Zheng, Zehao; Chen, Hao; Feng, Da (Frontiers in Pharmacology, 2021)
Introduction: A prevalence of polypharmacy is gradually increasing in geriatrics, which may contribute to adverse effects, such as potential drug-drug and drug-disease interactions. These side effects remain an important challenge in patient safety, which has a significant impact on mortality and incidence rate. Aims: Therefore, this study aims to understand the epidemiology of polypharmacy, and identify factors impact on management of potentially inappropriate prescribing. Methods: This study is a cross-sectional study, analyzing prescription data from720 hospitalized patients aged 50+ with random cluster sampling method. We used inverse probability treatment weighting (IPTW) method to group and match polypharmacy and non-polypharmacy patients, and logistic regression was conducted to explore the factors associated with polypharmacy. Results: Female (67.34%) have more polypharmacy than men, and key predictors associated with polypharmacy in the logistic regression model included: domicile (AOR=0.63, 95%CI 0.42-0.95) , annual income (AOR=0.38, 95%CI 0.20-0.70), the number of chronic diseases (AOR=3.68, 95%CI 2.69-5.06), taking Chinese medicine (AOR=1.70, 95%CI 1.22-2.36), decision involvement (AOR=0.67, 95%CI 0.49-0.91) , depression (AOR=1.42, 95%CI 1.03-1.96). Conclusion: Polypharmacy is common among the participants with chronic diseases in Hubei province, China. The study emphasizes that gerontology practitioners should be prudent in applying clinical guidelines to provide personalized, comprehensive assessment of decision-making of prescriptions, especially in socioeconomically deprived areas.